Decreased Levels of GSH Are Associated with Platinum Resistance in High-Grade Serous Ovarian Cancer - Daniela Criscuolo; Rosario Avolio; Matteo Parri; Simona Romano; Paola Chiarugi; Danilo Swann Matassa; Franca Esposito (Antioxidants, 2022)
High-grade serous ovarian cancer (HGSOC) is the most common and aggressive OC histotype. Although initially sensitive to standard platinum-based chemotherapy, most HGSOC patients relapse and become chemoresistant. We have previously demonstrated that platinum resistance is driven by a metabolic shift toward oxidative phosphorylation via activation of an inflammatory response, accompanied by reduced cholesterol biosynthesis and increased uptake of exogenous cholesterol. To better understand metabolic remodeling in OC, herein we performed an untargeted metabolomic analysis, which surprisingly showed decreased reduced glutathione (GSH) levels in resistant cells. Accordingly, we found reduced levels of enzymes involved in GSH synthesis and recycling, and compensatory increased expression of thioredoxin reductase. Cisplatin treatment caused an increase of reduced GSH, possibly due to direct binding hindering its oxidation, and consequent accumulation of reactive oxygen species. Notably, expression of the cysteine-glutamate antiporter xCT, which is crucial for GSH synthesis, directly correlates with post-progression survival of HGSOC patients, and is significantly reduced in patients not responding to platinum-based therapy. Overall, our data suggest that cisplatin treatment could positively select cancer cells which are independent from GSH for the maintenance of redox balance, and thus less sensitive to cisplatin-induced oxidative stress, opening new scenarios for the GSH pathway as a therapeutic target in HGSOC.